Adsorption of the Rhodamine B dye using rice husk ash - Severo, Fabiane Figueiredo; Muraro, Pâmela Cristine Ladwig; de Oliveira, Jivago Schumacher; Rodrigues Junior, Luiz Fernando; da Silva, William Leonardo; Zazycki, Maria Amélia (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Synthetic dyes have been used in various industrial processes, mainly in the textile, food, paper and paint sectors. It is of great environmental importance that the effluents generated in these industries are treated before being released into water resources. Adsorption is one of the most used methods in the treatment of water contaminated by dyes due to its high efficiency and low operating cost. Thus, the study investigated the potential use of rice husk ash for the removal of rhodamine B (RhB) dye in aqueous solution. Rice husk ash was obtained from the process of burning rice husk, without temperature and exposure time control and denominate CA1 and CA2. The ash was characterized regarding physical and chemical characteristics. The adsorption capacity was 2.59 and 3.25 mg g-1 for the ashes tested with a percentage of dye removal of 32.13% and 36.06% for CA1 and CA2, respectively. The adsorption kinetics of RhB on both ashes followed the pseudo-first order model. Equilibrium isotherms were well represented for the Langmuir and Freundlich model. In summary, it was possible to add value to rice ash residues, generating a low-cost adsorbent to treat colored effluents.